ETNOGRAFI KOMUNIKASI PADA MASYARAKAT BATAK TOBA DI KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA MENGENAI ANALISIS TINDAK TUTUR DALAM UPACARA KEMATIAN SAURMATUA - Hernawaty Hernawaty; Nancy Angelia Purba (Jurnal Darma Agung, 2019)
This research is aimed to know the type of speech act used in the death ceremony of Saurmatua Batak Toba and also defined the culture value in it. Method of research used is descriptive qualitative. The technique of data collection is observation, Interview, and literature. The technique of data analysis is to prepare the object of analysis, identifying and translating the data into Bahasa Indonesia, observing words and sentences, classifying the data, and then taking a conclusion. The research result found that there 41 illocution speech act, which is in the type of (1) directive act requesting, orders, asking, forcing, suggesting in 21 data or 511,22%, (2) representative act such as confessing, reporting, speculating in 16 data or 39,02%, and (3) expressive act such as thanking and criticizing in 4 data or 9,76%. Speech act in death ceremony of Saurmatua in Batak Toba Ethnicity is dominant by directive speech act.